Yerba mate aqueous extract improves the oxidative and inflammatory states of rats with adjuvant-induced arthritis. Issue 9 (22nd August 2019) - Correa, Vanesa Gesser; de Sá-Nakanishi, Anacharis B.; Gonçalves, Geferson de Almeida; Barros, Lillian; Ferreira, Isabel C. F. R.; Bracht, Adelar; Peralta, Rosane M.
Abstract : Healthy and adjuvant-induced arthritic rats were treated for 23 days with daily doses of 400 and 800 mg kg −1 Ilex paraguariensis extract. Abstract : Healthy and adjuvant-induced arthritic rats were treated for 23 days with daily doses of 400 and 800 mg kg −1 Ilex paraguariensis extract. This treatment (a) diminished the ROS levels in the liver and brain, (b) decreased oxidative protein and lipid damage in liver and brain, (c) increased the plasma antioxidant capacity, (d) increased the GSH levels and the GSH/GSSH ratio in both the liver and the brain, (e) almost restored the enzymatic activities linked to the metabolism of GSH–GSSG, and (f) reversed the modified activities of xanthine oxidase, superoxide dismutase and catalase. The anti-inflammatory actions (firstly) and the antioxidant actions (in the second place) of the yerba mate constituents ( e.g., chlorogenic acid derivatives) are the causes of these beneficial effects. Daily ingestion of traditional yerba mate beverages may be effective in attenuating the symptoms of inflammatory diseases, especially in older adults.